Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Use of mercury in mining 125 years ago continues to impact waterfowl populations: Implications for current artisanal gold mining - Morgan A. Byrne; Mae Sexauer Gustin; Chris A. Nicolai; Perry J. Williams (Science of The Total Environment, 2025)

Estimating coral reef carbonate budgets using Structure-from-Motion photogrammetry - Hannah C. Barkley; Ariel A. Halperin; Damaris Torres-Pulliza; Mia S. Lamirand; Courtney S. Couch; Candace E. Alagata; Rebecca M. Weible; Joy N. Smith; Thomas A. Oliver; Chris T. Perry (Coral Reefs, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Corrigendum to ‘The effect of ambient temperatures on hospital admissions for kidney diseases in Central Australia’ [Environ. Res. 259 (2024) 119502] - Mohammad Radwanur Talukder; Md Tauhidul Islam; Supriya Mathew; Chris Perry; Dung Phung; Shannon Rutherford; Alan Cass (Environmental Research, 2024)

Coral carbonate production across depth: homogenisation after bleaching? - Sivajyodee Sannassy Pilly; Ronan C. Roche; Ines D. Lange; Chris T. Perry; Andrew O. M. Mogg; Kathryn Dawson; John R. Turner (Coral Reefs, 2024)
Recurrent climate-driven warming events, which can induce severe coral bleaching and mortality on tropical reefs, are predicted to cause homogenisation of coral communities and loss of ecosystem functions in shallow reef systems (< 30 m). However, data documenting the variation in coral carbonate production across depth are limited. Here we explore differences in coral cover, community composition, coral colony size structure and carbonate production rates between two depths (10 m and 17.5 m) across four atolls in the remote Chagos Archipelago. We show higher coral carbonate production rates at 10 m (4.82 ± 0.27 G, where G = kg CaCO 3 m −2 yr −1 ) compared to sites at 17.5 m (3.1 ± 0.18 G). The main carbonate producers at 10 m consisted of fast-growing branching and tabular corals (mainly Acroporids) and massive corals (mainly Porites ), with high abundances of medium- and large-sized colonies. In contrast, coral carbonate production at 17.5 m was driven by slow-growing encrusting and foliose morphotypes and small colony sizes. Utilising a dataset following 6–7 years of recovery after the 2015–2017 bleaching event, our results show that depth-homogenisation of coral communities was temporary and carbonate production rates at 10 m depth recovered quicker at 3 of 4 studied atolls. The exception is Great Chagos Bank where slower recovery of branching and tabular corals at 10 m has led to a longer-lasting depth-homogenisation of carbonate production rates. The latter example cautions that more frequent bleaching events may drive increasing homogenisation of carbonate production rates across depth gradients, with implications for vital reef geo-ecological functions.

The effect of ambient temperatures on hospital admissions for kidney diseases in Central Australia - Mohammad Radwanur Talukder; Md Tauhidul Islam; Supriya Mathew; Chris Perry; Dung Phung; Shannon Rutherford; Alan Cass (Environmental Research, 2024)

Fine‐grained sediment production by endolithic sponges on Caribbean coral reefs - Didier M. de Bakker; Chris T. Perry; Eden Magaña‐Gallegos; Esmeralda Pérez‐Cervantes; Lorenzo Alvarez‐Filip (Limnology and Oceanography, 2024)
Endolithic sponges are key players in carbonate cycling on coral reef systems. While their bioerosion of reef framework is relatively well studied, their role in biogenic sediment generation is poorly understood. In this study, the sedimentary attributes and production rates of eight Caribbean endolithic sponge species were characterized. The findings revealed notable species‐specific variations in sediment production rates (range: 1.0–6.3 kg CaCO 3 m −2 yr −1 ), alongside consistency in sediment characteristics (modal sizes ranging from 39 to 48 μ m). The species‐specific rates were used to explore reef‐scale variations in sponge‐derived sediment generation across 50 reef sites in the Mexican Caribbean. Significant between‐site variability was observed, with estimated annual sediment production ranging from −2 of reef. Production was primarily driven by sponge abundance, with discernible spatial variations in the contributions of different species, which could be related to variability in local environmental conditions. The rapidity at which these sediment producers can utilize dead coral substrates, coupled with their positive response to the changing marine environment, highlights the growing importance of these sponges in modern degraded Caribbean reef systems.

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Quantifying endolithic bioerosion rates on remote coral reefs in the Central Indian Ocean - Jake E. Lloyd Newman; Chris T. Perry; Ines D. Lange (Coral Reefs, 2023)
Bioerosion of calcium carbonate is a fundamental process that impacts net coral reef accretion. Besides large grazers, endolithic organisms play a major role in carbonate removal. Here we provide the first rate data for both macro- and microendolithic bioerosion in the remote Chagos Archipelago, Indian Ocean. Based on analysis of experimental blocks using computer tomography, we show similar macrobioerosion rates at 5 m (0.086 ± 0.026 kg m −2 yr −1 ) compared to at 10 m depth (0.066 ± 0.016 kg m −2 yr −1 ) after three years of exposure, with a succession from worm to sponge bioeroders over time. Microbioerosion rates analysed with scanning electron microscopy were 2–5 × higher than macrobioerosion rates at 5 m (0.187 ± 0.028 kg m −2 yr −1 ) and 10 m depth (0.313 ± 0.049 kg m −2 yr −1 ), but the microborer community was dominated by cyanobacteria in all samples. Total endolithic erosion was small compared to external erosion by parrotfishes, which increased over time, but did not show significant differences between 5 m (0.74 ± 0.11) and 10 m depth (1.12 ± 0.16 kg m −2 yr −1 ) after three years of exposure. These erosion rates are indicative of the oligotrophic and remote reef setting in the Chagos Archipelago (clear water, low nutrients, high fish biomass). The data will help to improve local carbonate budget estimates and provide a context for wider regional and environmental comparisons.

Recovery trends of reef carbonate budgets at remote coral atolls 6 years post‐bleaching - Ines D. Lange; Chris T. Perry; Marleen Stuhr (Limnology and Oceanography, 2023)
Coral bleaching events and resultant changes in benthic community composition and population size structure can diminish the important geo‐ecological functions reefs provide, including habitat provision and carbonate production to support reef accretion. Net reef carbonate budgets, the balance between carbonate production and erosion processes, are thus important functional indicators of reef health. This study quantifies changes in coral community composition and colony size structures, and the resultant reef carbonate budget trajectories after the 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. ReefBudget surveys were conducted at 12 sites across three atolls in 2015, 2018, and 2021, with calculations of biological carbonate production and erosion supported by locally obtained calcification and bioerosion rates. Carbonate budgets (in G = kg CaCO 3 m −2 yr −1 ) shifted from net positive states in 2015 (mean ± SD: 3.8 ± 2.6 G) to net negative states in 2018 (−2.4 ± 1.4 G) in response to bleaching‐driven mass coral mortality. By 2021, all sites were on a trajectory of recovery, but net budgets differed significantly between atolls (−2.0 ± 1.7 to 2.2 ± 1.4 G). At Salomon atoll, the threefold faster recovery of carbonate production and return to positive reef budget states only 6 yr post‐bleaching was associated with the persistence of high structural complexity and the rapid recovery of fast growing tabular Acropora spp. Inter‐atoll differences in colony size distributions furthermore illustrate that coral identity and size class are more important predictors of reef functions and post‐disturbance recovery speed than coral cover alone.

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Coral reef erosion: In situ measurement on different dead coral substrates on a Caribbean reef - Ana Molina‐Hernández; Francisco Medellín‐Maldonado; Ines D. Lange; Chris T. Perry; Lorenzo Álvarez‐Filip (Limnology and Oceanography, 2022)
Widespread mortality of reef‐building coral substantially reduces the capacity for reef growth and makes available extensive bare substrate areas that in the absence of coral recovery will be eroded by a variety of external and internal bioeroders. Here, we analyze rates of external erosion on six different types of carbonate substrates under in situ conditions over a 2‐yr period. We measure vertical changes in the surface elevation of four species of recently dead corals afflicted by the stony coral tissue loss disease outbreak, and other two common types of calcareous substrates, long‐dead Acropora palmata fronds and bare calcareous hardground, as a reference for “bare” carbonate substrates that occur widely in Caribbean reefs. The surface of the recently dead colonies experienced significant erosion after 2 yr of exposure, but at different rates depending on the species. Dead skeletons of Orbicella faveolata experienced the greatest rates of erosion after 2 yr at −9.9 mm (±3.2 mm); Dendrogyra cylindrus eroded −3.6 mm (±2.8 mm), Pseudodiploria strigosa −3.3 mm (±3.7 mm), and Siderastrea siderea −1.2 mm (±0.9 mm), while long‐dead substrates remained unchanged. There was significant erosion in the presence of parrotfish grazing scars and of short algal turf mats, while crustose coralline algae cover and sand‐and‐high turf mats were not associated with significant changes in elevation, arguably indicating a protective effect. This study provides new insights into how and at what rates external carbonate erosion is shaping contemporary reefs at fine spatial and temporal scales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The importance of 1.5°C warming for the Great Barrier Reef - Jennifer K. McWhorter; Paul R. Halloran; George Roff; William J. Skirving; Chris T. Perry; Peter J. Mumby (Global Change Biology, 2022)
Tropical coral reefs are among the most sensitive ecosystems to climate change and will benefit from the more ambitious aims of the United Nations Framework Convention on Climate Change's Paris Agreement, which proposed to limit global warming to 1.5° rather than 2°C above pre‐industrial levels. Only in the latest Intergovernmental Panel on Climate Change focussed assessment, the Coupled Model Intercomparison Project phase 6 (CMIP6), have climate models been used to investigate the 1.5° warming scenario directly. Here, we combine the most recent model updates from CMIP6 with a semi‐dynamic downscaling to evaluate the difference between the 1.5 and 2°C global warming targets on coral thermal stress metrics for the Great Barrier Reef (GBR). By ~2080, severe bleaching events are expected to occur annually under intensifying emissions (shared socioeconomic pathway SSP5‐8.5). Adherence to 2° warming (SSP1‐2.6) halves this frequency but the main benefit of confining warming to 1.5° (SSP1‐1.9) is that bleaching events are reduced further to 3 events per decade. Attaining low emissions of 1.5° is also paramount to prevent the mean magnitude of thermal stress from stabilizing close to a critical thermal threshold (8 Degree Heating Weeks). Thermal stress under the more pessimistic pathways SSP3‐7.0 and SSP5‐8.5 is three to fourfold higher than the present day, with grave implications for future reef ecosystem health. As global warming continues, our projections also indicate more regional warming in the central and southern GBR than the far north and northern GBR.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

Enabling policy environment for water, food and energy security - Jelle Beekma; Jeremy Bird; Adey Nigatu Mersha; Stijn Reinhard; Sanmugam Ahembaranathan Prathapar; Golam Rasul; Jeffrey Richey; Jouke Van Campen; Ragab Ragab; Chris Perry; Rabi Mohtar; Laurie Tollefson; et al. (Irrigation and Drainage, 2021)
The complexity of water, food and energy security is analysed from the perspectives of (i) water and food and (ii) water and energy and their interconnectivity and focuses ultimately on water as a primary input into processes, the entry point for participants of the Third World Irrigation Forum. The paper provides an overview of trends in water, food and energy security, highlights the interconnectivity between the various elements and introduces the water–food–energy nexus as a tool for improving productivity and sector policies, avoiding unintended consequences on other sectors. Invariably, there will be trade‐offs and the challenge is to find combinations of measures that have a net positive outcome. In order to quantify security in the three elements and the trade‐offs between them, emerging modelling approaches for the nexus are discussed. Sub‐theme 3 of the forum focuses on productivity and technology interventions 1 and sub‐theme 2 on stakeholder interaction. The combination of modelling, technology innovations and stakeholder participation in a water–food–energy nexus approach leads to better understanding of linkages and more robust policies and is used to derive recommendations for an enabling policy environment.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Steps to Develop Early Warning Systems and Future Scenarios of Storm Wave-Driven Flooding Along Coral Reef-Lined Coasts - Gundula Winter; Curt Storlazzi; Sean Vitousek; Ap van Dongeren; Robert McCall; Ron Hoeke; William Skirving; John Marra; Johan Reyns; Jerome Aucan; Matthew Widlansky; Janet Becker; et al. (Frontiers in Marine Science, 2020)

Extreme spatial heterogeneity in carbonate accretion potential on a Caribbean fringing reef linked to local human disturbance gradients - Didier M. de Bakker; Fleur C. van Duyl; Chris T. Perry; Erik H. Meesters (Global Change Biology, 2019)
The capacity of coral reefs to maintain their structurally complex frameworks and to retain the potential for vertical accretion is vitally important to the persistence of their ecological functioning and the ecosystem services they sustain. However, datasets to support detailed along‐coast assessments of framework production rates and accretion potential do not presently exist. Here, we estimate, based on gross bioaccretion and bioerosion measures, the carbonate budgets and resultant estimated accretion rates (EAR) of the shallow reef zone of leeward Bonaire – between 5 and 12 m depth – at unique fine spatial resolution along this coast (115 sites). Whilst the fringing reef of Bonaire is often reported to be in a better ecological condition than most sites throughout the wider Caribbean region, our data show that the carbonate budgets of the reefs and derived EAR varied considerably across this ~58 km long fringing reef complex. Some areas, in particular the marine reserves, were indeed still dominated by structurally complex coral communities with high net carbonate production (>10 kg CaCO 3 m −2 year −1 ), high live coral cover and complex structural topography. The majority of the studied sites, however, were defined by relatively low budget states ( 3 m −2 year −1 ) or were in a state of net erosion. These data highlight the marked spatial heterogeneity that can occur in budget states, and thus in reef accretion potential, even between quite closely spaced areas of individual reef complexes. This heterogeneity is linked strongly to the degree of localized land‐based impacts along the coast, and resultant differences in the abundance of reef framework building coral species. The major impact of this variability is that those sections of reef defined by low‐accretion rates will have limited capacity to maintain their structural integrity and to keep pace with current projections of climate change induced sea‐level rise (SLR), thus posing a threat to reef functioning and biodiversity, potentially leading to trophic cascades. Since many Caribbean reefs are more severely degraded than those found around Bonaire, it is to be expected that the findings presented here are rather the rule than the exception, but the study also highlights the need for similar high spatial resolution (along‐coast) assessments of budget states and accretion rates to meaningfully explore increasing coastal risk at the country level. The findings also more generally underline the significance of reducing local anthropogenic disturbance and restoring framework building coral assemblages. Appropriately focussed local preservation efforts may aid in averting future large‐scale above reef water depth increases on Caribbean coral reefs and will limit the social and economic implications associated with the loss of reef goods and services.

Calcium carbonate production by fish in temperate marine environments - Michael A. Salter; Chris T. Perry; Abigail M. Smith (Limnology and Oceanography, 2019)
Marine bony fishes are an important source of calcium carbonate with relevance to sediment production and inorganic carbon cycling. However, knowledge of the production and fate of these carbonates is based primarily on data from warm‐water reef fishes, with efforts to assess global‐scale implications constrained by assumptions that this small cross section of the global fish community is widely representative. Here we test the extent to which temperature influences fish carbonate mineralogy and morphology by comparing products from temperate settings (20 species at temperatures spanning 10–18°C) against existing data (23–27°C). Overall, carbonate products were mineralogically, compositionally, and morphologically similar throughout the thermal range, and in most cases, we observed no differences within species (18 vs. 24°C) or families (10 vs. 25°C). Confirmation of within‐family consistency over large thermal gradients is significant because: (1) it facilitates a substantial range expansion over which fish carbonate production models can be constructed, even where family‐level product data are geographically limited; and (2) it implies that the solubility of products from any given fish family varies only due to local carbonate saturation states at excretion (and not crystallographic differences). The only exception was in two members of the Labridae (wrasses), which produced low‐Mg calcite (LMC) and minor amorphous calcium–magnesium carbonate (ACMC) at 10°C; the inverse of products from confamilials at 25°C. This finding could have significant implications for understanding the role of fish carbonates globally because ACMC is a highly unstable carbonate polymorph, whereas LMC is very stable.

Bleaching impacts on carbonate production in the Chagos Archipelago: influence of functional coral groups on carbonate budget trajectories - Ines D. Lange; Chris T. Perry (Coral Reefs, 2019)

Temporal relationship between the Lassen volcanic center and mafic regional volcanism - Aurelie Germa; Chris Perry; Xavier Quidelleur; Andrew Calvert; Michael Clynne; Charles B. Connor; Laura J. Connor; Rocco Malservisi; Sylvain Charbonnier (Bulletin of Volcanology, 2019)

Census Estimates of Algal and Epiphytic Carbonate Production Highlight Tropical Seagrass Meadows as Sediment Production Hotspots - Chris T. Perry; Michael A. Salter; Kyle M. Morgan; Alastair R. Harborne (Frontiers in Marine Science, 2019)

Increased alertness, better than posture prioritization, explains dual-task performance in prosthesis users and controls under increasing postural and cognitive challenge - Charla L. Howard; Bonnie Perry; John W. Chow; Chris Wallace; Dobrivoje S. Stokic (Experimental Brain Research, 2017)

Mapping novel aphid resistance QTL from wild soybean, Glycine soja 85-32 - Shichen Zhang; Zhongnan Zhang; Carmille Bales; Cuihua Gu; Chris DiFonzo; Ming Li; Qijian Song; Perry Cregan; Zhenyu Yang; Dechun Wang (Theoretical and Applied Genetics, 2017)

Nearshore Turbid-Zone Corals Exhibit High Bleaching Tolerance on the Great Barrier Reef Following the 2016 Ocean Warming Event - Kyle M. Morgan; Chris T. Perry; Jamie A. Johnson; Scott G. Smithers (Frontiers in Marine Science, 2017)

Reef Habitat Type and Spatial Extent as Interacting Controls on Platform-Scale Carbonate Budgets - Chris T. Perry; Kyle M. Morgan; Robert T. Yarlett (Frontiers in Marine Science, 2017)

Regional‐scale dominance of non‐framework building corals on Caribbean reefs affects carbonate production and future reef growth - Chris T. Perry; Robert S. Steneck; Gary N. Murphy; Paul S. Kench; Evan N. Edinger; Scott G. Smithers; Peter J. Mumby (Global Change Biology, 2015)
Coral cover on Caribbean reefs has declined rapidly since the early 1980's. Diseases have been a major driver, decimating communities of framework building Acropora and Orbicella coral species, and reportedly leading to the emergence of novel coral assemblages often dominated by domed and plating species of the genera Agaricia , Porites and Siderastrea . These corals were not historically important Caribbean framework builders, and typically have much smaller stature and lower calcification rates, fuelling concerns over reef carbonate production and growth potential. Using data from 75 reefs from across the Caribbean we quantify: (i) the magnitude of non‐framework building coral dominance throughout the region and (ii) the contribution of these corals to contemporary carbonate production. Our data show that live coral cover averages 18.2% across our sites and coral carbonate production 4.1 kg Ca CO 3 m −2 yr −1 . However, non‐framework building coral species dominate and are major carbonate producers at a high proportion of sites; they are more abundant than Acropora and Orbicella at 73% of sites; contribute an average 68% of the carbonate produced; and produce more than half the carbonate at 79% of sites. Coral cover and carbonate production rate are strongly correlated but, as relative abundance of non‐framework building corals increases, average carbonate production rates decline. Consequently, the use of coral cover as a predictor of carbonate budget status, without species level production rate data, needs to be treated with caution. Our findings provide compelling evidence for the Caribbean‐wide dominance of non‐framework building coral taxa, and that these species are now major regional carbonate producers. However, because these species typically have lower calcification rates, continued transitions to states dominated by non‐framework building coral species will further reduce carbonate production rates below ‘predecline’ levels, resulting in shifts towards negative carbonate budget states and reducing reef growth potential.

The spatial distribution of canopy-resident and ground-resident cereal aphids (Sitobion avenae and Metopolophium dirhodum) in winter wheat - Linton Winder; Colin J. Alexander; Chris Woolley; Joe N. Perry; John M. Holland (Arthropod-Plant Interactions, 2013)

Evolutionary genetics of the human Rh blood group system - George H. Perry; Yali Xue; Richard S. Smith; Wynn K. Meyer; Minal Çalışkan; Omar Yanez-Cuna; Arthur S. Lee; María Gutiérrez-Arcelus; Carole Ober; Edward J. Hollox; Chris Tyler-Smith; Charles Lee (Human Genetics, 2012)

Implications of reef ecosystem change for the stability and maintenance of coral reef islands - Chris T. Perry; Paul S. Kench; Scott G. Smithers; Bernhard Riegl; Hiroya Yamano; Michael J. O'Leary (Global Change Biology, 2011)
Coral reef islands are among the most vulnerable environments on Earth to climate change because they are low lying and largely constructed from unconsolidated sediments that can be readily reworked by waves and currents. These sediments derive entirely from surrounding coral reef and reef flat environments and are thus highly sensitive to ecological transitions that may modify reef community composition and productivity. How such modifications – driven by anthropogenic disturbances and on‐going and projected climatic and environmental change – will impact reef island sediment supply and geomorphic stability remains a critical but poorly resolved question. Here, we review the unique ecological–geomorphological linkages that underpin this question and, using different scenarios of environmental change for which reef sediment production responses can be projected, explore the likely resilience of different island types. In general, sand‐dominated islands are likely to be less resilient than those dominated by rubble grade material. However, because different islands typically have different dominant sediment constituents (usually either coral, benthic foraminifera or H alimeda ) and because these respond differently to individual ecological disturbances, island resilience is likely to be highly variable. Islands composed of coral sands are likely to undergo major morphological change under most near‐future ecological change scenarios, while those dominated by H alimeda may be more resilient. Islands composed predominantly of benthic foraminifera (a common state through the P acific region) are likely to exhibit varying degrees of resilience depending upon the precise combination of ecological disturbances faced. The study demonstrates the critical need for further research bridging the ecological–geomorphological divide to understand: (1) sediment production responses to different ecological and environmental change scenarios; and (2) dependant landform vulnerability.

Remote Sensing and Economic Indicators for Supporting Water Resources Management Decisions - Petra J. G. J. Hellegers; Richard Soppe; Chris J. Perry; Wim G. M. Bastiaanssen (Water Resources Management, 2010)

Stabilisation of intertidal cobbles and gravels by Goniastrea aspera: an analogue for substrate colonisation during marine transgressions? - Chris T. Perry; Scott G. Smithers (Coral Reefs, 2009)

Reply: Efficient irrigation; inefficient communication; flawed recommendations: response to comment - Chris Perry (Irrigation and Drainage, 2008)

Efficient irrigation; inefficient communication; flawed recommendations - Chris Perry (Irrigation and Drainage, 2007)
Concerns about scarcity of water have focused attention on irrigation, the largest water‐using sector worldwide, which is widely seen as a low‐value, wasteful and “inefficient” use for water. The terminology for this debate is, however, poorly defined – often failing even to distinguish between consumptive and non‐consumptive uses. In consequence, technical interventions have not always led to the expected, desirable outcomes, and the recommendations in many reports and papers are at best dubious, at worst simply wrong. The history of the analysis of “irrigation efficiency” is traced, and compared with the science of hydrology, which offers consistent terminology for various scales of analysis from field through irrigation scheme to region and basin. Based on the work of various previous writers, an analytical framework and associated terms are proposed to better serve the needs of technical specialists from all water‐using sectors, policymakers and planners in achieving more productive use of water and tracing the implications of interventions on other uses and users. ICID recommends that this terminology be used in the analysis of water resources management at all scales, and form the basis for its research papers and other published outputs. Copyright © 2007 John Wiley & Sons, Ltd.

In Situ Instrumentation - John Paul; Chris Scholin; Ger van den Engh; Mary Jane Perry (Oceanography, 2007)

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2006)

Prefrontal GABA levels in cocaine-dependent subjects increase with pramipexole and venlafaxine treatment - Chris C. Streeter; John Hennen; Yong Ke; J. Eric Jensen; Ofra Sarid-Segal; Leanne E. Nassar; Clifford Knapp; Angela A. Meyer; Tae Kwak; Perry F. Renshaw; Domenic A. Ciraulo (Psychopharmacology, 2005)

Methods of screening apricot fruit for resistance to brown rot caused by Monilinia spp. - Monika Walter; Gillian F. McLaren; Jenny A. Fraser; Chris M. Frampton; Kirsty S. H. Boyd-Wilson; Joanne H. Perry (Australasian Plant Pathology, 2004)

Increasing water productivity through deficit irrigation: evidence from the Indus plains of Pakistan - Asad Sarwar; Chris Perry (Irrigation and Drainage, 2002)
Water shortage shifts attention from the traditional concept of crop yield—production per unit of land—to the productivity of water—production per unit of water. Whether this parameter is best increased through responsive, sophisticated irrigation scheduling or through predetermined schedules, providing limited water, has been a contentious issue for some years. This paper brings together modelling studies from Pakistan that address this issue, as well as raising the question of whether deficit irrigation threatens sustainability through the build‐up of salts in the soil profile. It is shown that under conditions of plentiful water, highest productivity is achieved when irrigation is precisely scheduled to meet crop needs. However, when water is short its productivity is substantially increased (by almost 50%) by deficit irrigation. No salt problem occurs as long as amount of water applied through irrigation is sufficient to meet 80% of the total crop evapotranspiration. Under limited water conditions, the productivity achieved is little affected by setting predetermined irrigation schedules, allowing the operating agency to concentrate on reliability of service. Finally, it is also shown that the salt build‐up is independent of irrigation scheduling. Copyright © 2002 John Wiley & Sons, Ltd.

Modelling the dynamic spatio‐temporal response of predators to transient prey patches in the field - Linton Winder; Colin J. Alexander; John M. Holland; Chris Woolley; Joe N. Perry (Ecology Letters, 2001)
The spatio‐temporal dynamics of two aphid species ( Metopolophium dirhodum and Sitobion avenae ) and a generalist predator ( Pterostichus melanarius ) were observed in a field‐scale study using a grid of 256 sampling locations with a 12‐m spacing. Using Spatial Analysis by Distance Indices we demonstrate that populations show ephemeral spatial pattern at the field scale. We observed a positive, lagged beetle response to this aphid pattern; conversely, the aphids displayed a negative, lagged response to beetle spatial pattern. Examination of the local structure of the spatio‐temporal dynamics revealed a strong response by the beetle population to aphid patches. The temporal structure of spatial associations between the species shows a strong correspondence with those from a conceptual model of predator–prey spatial interaction. The spatially coupled dynamics were sufficiently strong for the predator to have a negative effect on the intrinsic rate of increase of their prey.

World Commission on Dams: implications for food and irrigation 1 1 - Chris Perry (Irrigation and Drainage, 2001)
The World Commission on Dams has now published its report. Insights into the workings and conclusions of the Commission were published in the last edition of this Journal. While the WCD report brings together a number of important existing and new recommendations on ameliorating the negative impacts of large dams, it pays inadequate attention to the impacts in the major area (food production and security) for which dams have been built. Consideration of data presented by the WCD would suggest a more positive impact, and a brief review of national and world trends in food production suggests that irrigation – of which large dams are an intrinsic and central component – has underlain if not dominated the vast improvement in food availability that occurred in the second half of the last century. With water in crisis in many countries, planners, policymakers and politicians will continue to face challenging decisions on the allocation of limited freshwater supplies, and demands to increase the level of water resources development. Some guidance from the WCD is helpful, and some is flawed. Most importantly, much is missing, and to be useful, guidance must reflect rational and balanced, expert and rigorous assessment of all the impacts of the available options. Copyright © 2001 John Wiley & Sons, Ltd.

Water at any price? Issues and options in charging for irrigation water1 - Chris Perry (Irrigation and Drainage, 2001)
Shortage of water and inadequate funding for maintenance of irrigation works have focused attention on the potential for water charges to generate financial resources, and reduce demand for water through volume‐based charges. Examples from other utilities, and from the domestic/industrial sectors of water supply, suggest the approach could be effective. However, in many developing countries, the facilities required for measured and controlled delivery, which are both essential for volume‐related charges, are not in place and their introduction would require a massive investment in physical, legal and administrative infrastructure. To be effective in curtailing demand, the price of water must be significant, but the price structures and levels that are within the politically feasible and acceptable range are usually too low to have a real impact on demand, much less to actually bring supply and demand into balance. Similarly, the present cost of water is too low to induce significant technical innovation or investments that could reduce consumption. Moreover, while water supplied is a proper measure of service in domestic and industrial uses, in irrigation, and especially as the water resource itself becomes constrained, water consumption is the appropriate measure for water accounting, and this is exceptionally difficult to define. An alternative approach to coping with shortage would focus on assigning volumes to specific uses – and effectively rationing water where demand exceeds supply – has a number of potential benefits including simplicity, transparency and the potential to tailor allocations specifically to hydrological situations. Copyright © 2001 John Wiley & Sons Ltd.

Synthesis, Fabrication, and Photoluminescence of CaF2 Doped with Rare Earth Ions - Eric Faulques; Jany Wery; Bertrand Dulieu; Chris Seybert; Dale L. Perry (Journal of Fluorescence, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)